Why Medical Informatics (still) Needs Cognitive and Social Sciences - Declerck, G.; Aimé, X. (Yearbook of Medical Informatics, 2013)
Objectives: To summarize current excellent medical informatics research in the field of human factors and organizational issues.Methods: Using PubMed, a total of 3,024 papers were selected from 17 journals. The papers were evaluated on the basis of their title, keywords, and abstract, using several exclusion and inclusion criteria. 15 preselected papers were carefully evaluated by six referees using a standard evaluation grid.Results: Six best papers were selected exemplifying the central role cognitive and social sciences can play in medical informatics research. Among other contributions, those studies: (i) make use of the distributed cognition paradigm to model and understand clinical care situations; (ii) take into account organizational issues to analyse the impact of HIT on information exchange and coordination processes; (iii) illustrate how models and empirical data from cognitive psychology can be used in medical informatics; and (iv) highlight the need of qualitative studies to analyze the unexpected side effects of HIT on cognitive and work processes.Conclusion: The selected papers demonstrate that paradigms, methodologies, models, and results from cognitive and social sciences can help to bridge the gap between HIT and end users, and contribute to limit adoption failures that are reported regularly.
Keywords: Medical informatics; International Medical Informatics Association; human factors; organizational issues; cognitive sciences; social sciences